CD40- and CD95-specific antibody single chain-Baff fusion proteins display BaffR-, TACI- and BCMA-restricted agonism. Issue 1 (1st January 2020) - Nelke, Johannes; Medler, Juliane; Weisenberger, Daniela; Beilhack, Andreas; Wajant, Harald
ABSTRACT: Antibodies that target a clinically relevant group of receptors within the tumor necrosis factor receptor superfamily (TNFRSF), including CD40 and CD95 (Fas/Apo-1), also require binding to Fc gamma receptors (FcγRs) to elicit a strong agonistic activity. This FcγR dependency largely relies on the mere cellular anchoring through the antibody's Fc domain and does not involve the engagement of FcγR signaling. The aim of this study was to elicit agonistic activity from αCD40 and αCD95 antibodies in a myeloma cell anchoring-controlled FcγR-independent manner. For this purpose, various antibody variants (IgG1, IgG1N297A, Fab2 ) against the TNFRSF members CD40 and CD95 were genetically fused to a single-chain-encoded B-cell activating factor (scBaff) trimer as a C-terminal myeloma-specific anchoring domain substituting for Fc domain-mediated FcγR binding. The antibody-scBaff fusion proteins were evaluated in binding studies and functional assays using tumor cell lines expressing one or more of the three receptors of Baff: BaffR, transmembrane activator and CAML interactor (TACI) and B-cell maturation antigen (BCMA). Cellular binding studies showed that the binding properties of the different domains within the fusion proteins remained fully intact in the antibody-scBaff fusion proteins. In co-culture assays of CD40- and CD95-responsive cells with BaffR, BCMA or TACI expressing anchoring cells, the antibody fusion proteins displayed strong agonism while only minor receptor stimulation was observed in co-cultures with cells without expression of Baff-interacting receptors. Thus, our CD40 and CD95 antibody fusion proteins display myeloma cell-dependent activity and promise reduced systemic side effects compared to conventional CD40 and CD95 agonists.